2018
DOI: 10.2139/ssrn.3244885
|View full text |Cite
|
Sign up to set email alerts
|

GSK3β Activity Alleviates Epileptogenesis and Limits GluA1 Phosphorylation

Abstract: GSK3β activity alleviates epileptogenesis and limits GluA1 phosphorylation Urbanska, M.; Kazmierska-Grebowska, P.; Kowalczyk, T.; Caban, B.; Nader, K.; Pijet, B.; Kalita, K.; Gozdz, A.; Devijver, H.; Lechat, B.; Jaworski, T.; Grajkowska, W.; Sadowski, K.; Jozwiak, S.; Kotulska, K.; Konopacki, J.; Van Leuven, F.; van Vliet, E.A.; Aronica, E.; Jaworski, J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…40 In contrast, a genetic mouse model with low GSK3α/β activity displayed greater seizure severity during kainate-induced SE 30 and constitutive GSK3β activation in mice reduced susceptibility to kainate-induced seizures. 41 Gys1 mRNA levels were unaffected in the hippocampal formations of chronic CSE mice. If translated, lowered Gsk3b mRNA levels are expected to influence GYS1 only via post-translational modification.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…40 In contrast, a genetic mouse model with low GSK3α/β activity displayed greater seizure severity during kainate-induced SE 30 and constitutive GSK3β activation in mice reduced susceptibility to kainate-induced seizures. 41 Gys1 mRNA levels were unaffected in the hippocampal formations of chronic CSE mice. If translated, lowered Gsk3b mRNA levels are expected to influence GYS1 only via post-translational modification.…”
Section: Discussionmentioning
confidence: 90%
“…A study using rat pilocarpine and mouse 6 Hz models found pharmacological inhibition of GSK3β lowered seizure susceptibility 40 . In contrast, a genetic mouse model with low GSK3α/β activity displayed greater seizure severity during kainate‐induced SE 30 and constitutive GSK3β activation in mice reduced susceptibility to kainate‐induced seizures 41 …”
Section: Discussionmentioning
confidence: 99%
“…Variants in BRCA1-associated protein required for ATM activation-1 cause multifocal seizure syndrome [32, 33]. GSK3B activity protects neuronal networks from hyperactivation in response to epileptogenic stimuli [34]. Given that some main hubs of PPIN are closely related to epilepsy, they are likely to be important molecules regulated by CZD in treatment of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Mean gray values of every other sample are presented as ratios. Quantitative analysis of S6, Akt, and GluA1 phosphorylation levels was performed using the Infrared Odyssey Imaging System (LI-COR Biosciences) described previously (Urbanska et al, 2018, Urbanska et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Following incubation, they were washed three times for 10 min each in TBST and then incubated for 1.5-2 h in HRP-conjugated secondary antibody diluted in 2.5% milk in TBST. Finally, blots were developed for ~2-3 min in a freshly made chemiluminescence developing buffer (100 mM Tris phosphorylation levels was performed using the Infrared Odyssey Imaging System (LI-COR Biosciences) described previously (Urbanska et al, 2018, Urbanska et al, 2019.…”
Section: Western Blotmentioning
confidence: 99%